STUDENTS’ THINKING PROCESS IN INVESTIGATING MATHEMATICAL STATEMENT - Siti Faizah; Sudirman Sudirman (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
The statement is a declaratif sentence that can be true or false. It can’t do both at the same time so it needs an investigation through proving process. This research aims to explore the students’ thinking process in investigating the truth value of matematical statement. This research is conducted to seventeen students of mathematical education whom are taking the Abstract Algebra Course. The subject selecting in this reasearch is based on the students’ ability in doing the investigating by using formal proof. The data collecting uses the written test and the interview. Meanwhile, the data analysis is conducted through three steps: data reduction, data interpretation, and taking a conclusion. Based on the result of the research, it is found that students do the thinking process in investigating the matematical statements’ truth value through four steps. The first step, students understand the statements by reading them and classifying them to be a number of objects. The second one, students determine the proof startegies based on the definition or axiom. The third one, students do the algebraic operation by using symbol manipulation. The last one, students provide justification as the form of their belief of the proof results.